2020
DOI: 10.1101/2020.10.15.340943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypoxia pathway proteins regulate the synthesis and release of epinephrine in the mouse adrenal gland

Abstract: The adrenal gland and its hormones regulate numerous fundamental biological processes; however, the impact of hypoxia signalling on its function remains scarcely understood. Here, we reveal that deficiency of HIF (Hypoxia Inducible Factors) prolyl hydroxylase domain protein-2 (PHD2) in the adrenal medulla of mice results in HIF2α-mediated reduction in phenylethanolamine N-methyltransferase (PNMT) expression, and consequent reduction in epinephrine synthesis. Concomitant loss of PHD2 in renal erythropoietin (EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…During birth, increased catecholamine release facilitates adequate hemodynamic adjustment and stimulates surfactant production by the lungs (73, 74). A deficiency of Phd2 in the adrenal medulla of mice results in a Hif2a-mediated reduction in phenylethanolamine N-methyltransferase (Pnmt) associated with a reduced epinephrine biosynthesis (75). This is also consistent with studies in Hif2a -/mice, which showed reduced epinephrine levels in the adrenal gland (68,76).…”
Section: Hif Signaling During Neural Crest and Adrenal Developmentsupporting
confidence: 72%
“…During birth, increased catecholamine release facilitates adequate hemodynamic adjustment and stimulates surfactant production by the lungs (73, 74). A deficiency of Phd2 in the adrenal medulla of mice results in a Hif2a-mediated reduction in phenylethanolamine N-methyltransferase (Pnmt) associated with a reduced epinephrine biosynthesis (75). This is also consistent with studies in Hif2a -/mice, which showed reduced epinephrine levels in the adrenal gland (68,76).…”
Section: Hif Signaling During Neural Crest and Adrenal Developmentsupporting
confidence: 72%